The Politics of Local Government - Stoker, Gerry. author. aut Link
XVII, 294 p.
Keywords: The last decade has seen an increase in political and ideological conflict in local government. This book analyzes this context and examines both the operation of elected local authorities and the rise of a non-directly elected local governement.